Culture, Inculturation, and Theologians : A Postmodern Critique - Arbuckle, Gerald A. (Book collections on Project MUSE., 2010)
"Combining his immense learning in anthropology and theology with his deep concern for the Christian faith Arbuckle again puts all of us scholars and church leaders in his debt with this splendid volume. With his characteristically limpid prose and thought-provoking insights our prolific author forces us to rethink entirely the relation between faith and culture in our postmodern age. This is a landmark book, and the future of Christianity and Christian mission may well depend on how its proposals are taken seriously and put into practice."--Jacket